2011
DOI: 10.14210/bjast.v15n1.p71-77
|View full text |Cite
|
Sign up to set email alerts
|

Fitoplâncton de uma Lagoa de Estabilização no Nordeste do Brasil

Abstract: The study of phytoplanktonic organisms has grown in recent times, as a consequence of its importance in several aquatic ecosystems, both in continental and marine environments. In stabilization ponds, for example, they act in the biological treatment of sewage. These ponds are an eutrophic environment, characterized by a considerable growth of phytoplankton. To study the phytoplankton composition in such ponds, samples were collected in a facultative pond in a sewage treatment station, located in Barbalha (Cea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
6
1
2
Order By: Relevance
“…The genera of cyanobacteria found in the present study differ little from those recorded by Aquino (2010) and Aquino (2011) Six species of cyanobacteria were common in the ten studied ponds: M. tenuissima, Aphanocapsa sp, Lyngbya sp, Pseudanabaena sp, Microcystis sp e Spirulina sp. On average, M. tenuissima appeared more, suggesting that this species best adapts to the hypereutrophic environment of the ponds.…”
Section: Resultscontrasting
confidence: 86%
“…The genera of cyanobacteria found in the present study differ little from those recorded by Aquino (2010) and Aquino (2011) Six species of cyanobacteria were common in the ten studied ponds: M. tenuissima, Aphanocapsa sp, Lyngbya sp, Pseudanabaena sp, Microcystis sp e Spirulina sp. On average, M. tenuissima appeared more, suggesting that this species best adapts to the hypereutrophic environment of the ponds.…”
Section: Resultscontrasting
confidence: 86%
“…), c-strategist, in both ponds, as observed by Aquino et al (2011). These organisms are abundant in shallow water bodies with higher concentration of nutrients (Padisák et al, 2009).…”
Section: Discussionmentioning
confidence: 69%
“…However, it should be considered that lower biodiversity may decrease the magnitude and stability of the ecosystem processes, such as the use of resources and productivity (Cottingham et al, 2001;Ptacnik et al, 2008). Delazari-Barroso et al (2009) had reported such event in Brazil, with 38 taxa in the polishing ponds; Aquino et al (2011) also identified 22 phytoplankton taxa in the facultative pond. Cyanobacteria had a major contribution regarding both richness (mean of 9 taxa per sample) and phytoplankton abundance (high contribution of Pseudanabaena mucicola in February 2012), which may be common in this type of environment, where it prevails over other phytoplankton groups (Furtado et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, a comunidade fitoplanctônica é amplamente utilizada em estudos de biomonitoramento de corpos hídricos (CARVALHO, 2003) em função da sua capacidade ecológica em responder rapidamente a qualquer estímulo externo, como por exemplo, aos processos de poluição e contaminação do meio aquático. Estes organismos são muito utilizados como bioindicadores da qualidade ambiental (AQUINO et al, 2011;LOPES, 2007;PEREIRA, 2007).…”
Section: Introductionunclassified